Fetal and maternal responses to high feed intake from day 29 to 45 of gestation - Musser, R.E.; Smith, J.W.II; Burum, L.L.; Samland, C.J.; Davis, Duane L.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Rathbun, Theresa J.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Parity-four sows were fed either 4.0 Ib/d (control, n = 6) or 14.0 Ib/d (high, n = 9) of feed from d 29 to 45 of gestation. On d 45 of ges~tion, sows were slaughtered and uteri collected for fetal and placental measurements. High-feed-intake sows gained more weight from. d 29 to 45 compared to control sows. Providing feed in excess of established requirements to gestating sows from d 29 to 45 of gestation increased IGF-I concentrations in maternal plasma and decreased crown-rump length variation of the fetus. Increased feed intake resulted in a removal of the correlation between average fetal weight and number of fetuses per sow. We postulate that the increased maternal IGF-I or other maternal responses to high feed intake altered the maternal limit on fetal growth at this stage of gestation.
Keywords: Swine; Feed intake; Fetal growth; Insulin-like growth factor